2017
DOI: 10.3389/fpsyg.2017.00030
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Visual Field Asymmetries for Face Categorization in Early Deaf Adults: A Study With Chimeric Faces

Abstract: Right hemisphere lateralization for face processing is well documented in typical populations. At the behavioral level, this right hemisphere bias is often related to a left visual field (LVF) bias. A conventional mean to study this phenomenon consists of using chimeric faces that are composed of the left and right parts of two faces. In this paradigm, participants generally use the left part of the chimeric face, mostly processed through the right optic tract, to determine its identity, gender or age. To asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
5
0
3
Order By: Relevance
“…In bisection tasks, this could, in theory, lead to the left side being perceived as longer so that the perceived centre is shifted towards the left side. Prior findings suggest that the left hemisphere may be recruited to a greater extent in deaf than in hearing individuals by visuospatial tasks tapping on different abilities, such as motion discrimination, spatial processing, and face processing (e.g., Bosworth, Petrich, & Dobkins, 2013; Brozinsky & Bavelier, 2004; Cattani & Clibbens, 2005; Dole, Méary, & Pascalis, 2017; Weisberg, Koo, Crain, & Eden, 2012; but see Dye, Seymour, & Hauser, 2016), a finding that likely depends on both sensory deprivation per se and sign language use. Accordingly, in a prior study (Cattaneo, Lega, Cecchetto, & Papagno, 2014), we found that deaf individuals (irrespective of sign language use) did not show any systematic bias in bisecting visual lines, whereas hearing controls showed the typical tendency to over-represent the left portion of space (i.e., pseudoneglect).…”
Section: Introductionmentioning
confidence: 99%
“…In bisection tasks, this could, in theory, lead to the left side being perceived as longer so that the perceived centre is shifted towards the left side. Prior findings suggest that the left hemisphere may be recruited to a greater extent in deaf than in hearing individuals by visuospatial tasks tapping on different abilities, such as motion discrimination, spatial processing, and face processing (e.g., Bosworth, Petrich, & Dobkins, 2013; Brozinsky & Bavelier, 2004; Cattani & Clibbens, 2005; Dole, Méary, & Pascalis, 2017; Weisberg, Koo, Crain, & Eden, 2012; but see Dye, Seymour, & Hauser, 2016), a finding that likely depends on both sensory deprivation per se and sign language use. Accordingly, in a prior study (Cattaneo, Lega, Cecchetto, & Papagno, 2014), we found that deaf individuals (irrespective of sign language use) did not show any systematic bias in bisecting visual lines, whereas hearing controls showed the typical tendency to over-represent the left portion of space (i.e., pseudoneglect).…”
Section: Introductionmentioning
confidence: 99%
“…而语言加工的神经中枢位于左半球,因此听障个体在加工表情会显著激活大脑 左半球的语言中枢,从而导致表情加工右脑优势效应的减弱或消失 [28] . 尽管对听障个体表情加 工的偏侧化特点得到了较多的研究,但是目前很少有研究关注听障个体中性面孔加工的偏侧化 特点 [33] . 对听障个体中性面孔加工的偏侧化特点研究不但能加深我们对听障个体视知觉特点 的理解,还能更好地揭示人类面孔加工偏侧化的形成是如何受经验的影响.…”
Section: 以上研究也表明面孔识别能力的发展并不是独立的, 其他知觉经验的获得也会影响面孔识 别能力的发展 此外,早期知觉经验的剥夺也会对面孔识别能力的发展产生影响 例如,Leunclassified
“…对听障个体中性面孔加工的偏侧化特点研究不但能加深我们对听障个体视知觉特点 的理解,还能更好地揭示人类面孔加工偏侧化的形成是如何受经验的影响. Dole 等人 [33] [34,35] . 并且,以往关于听障个体表情加工的研究表明,任务的 性质也会影响到表情加工的偏侧化效应 [28,36] .…”
Section: 以上研究也表明面孔识别能力的发展并不是独立的, 其他知觉经验的获得也会影响面孔识 别能力的发展 此外,早期知觉经验的剥夺也会对面孔识别能力的发展产生影响 例如,Leunclassified
See 1 more Smart Citation
“…A compelling illustration of the multisensorial integration of speech is the McGurk effect (McGurk and MacDonald, 1976). During ecological face-to-face interactions, perception of the speaker's orofacial articulatory movements offers critical complementary information for speech perception during infancy (Weikum et al, 2007;Lewkowicz and Hansen-Tift, 2012;Sebastián-Gallés et al, 2012;Tenenbaum et al, 2012), speech-in-noise perception (Sumby and Pollack, 1954;Ross et al, 2006), for non-native speech processing (Navarra and Soto-Faraco, 2005;Hirata and Kelly, 2010) and for people with hearing difficulties (Bernstein et al, 2000;Auer and Bernstein, 2007;Letourneau and Mitchell, 2013;Dole et al, 2017;Worster et al, 2017).…”
Section: Visemes-phoneme Bindingmentioning
confidence: 99%